Міжмовні лексико-семантичні відношення (на матеріалі англійської та української фразеології) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The paper examines the problem of interlingual relations at the lexical level. It studies the cases of equivalence, inclusion, overlapping and non-equivalence in the systems of English and Ukrainian phraseology.